Occupational health risk assessment based on actual dust exposure in a tunnel construction adopting roadheader in Chongqing, China. (November 2019) - Chen, Xiaofeng; Guo, Chun; Song, Junxiu; Wang, Xin; Cheng, Jianghao
Abstract: Tunnel construction, especially those excavated by roadheader, will produce great dust pollution, which always result in serious health risks to workers. In order to reveal the health risk characteristics of tunnel construction dust and improve the workers' occupational health level, combining the tunnel construction characteristics, this paper established a health risk assessment system based on field measurement. The assessment system consisted of exposure assessment and risk quantification adopting disability-adjusted life year(DALY). Then, the willingness to pay(WTP) was employed to monetize health risk and endow health risk with economic significance, that is, the cost to reduce risk. In this paper, the isolation effect of dust masks in tunnel construction was taken into account for the first time, and the dust exposure concentration of workers was corrected by a unique formula according to the inward leakage(IL) and filtration efficiency(FE). The results showed that the isolation of masks obviously reduced the health risk, in which health risk was drastically reduced by 82% under ideal isolation effect and by 26% under actual isolation effect. In each procedure, the health risk of tunneling was the greatest, followed by slag-out, and the smallest was lining. In addition, although the dust pollution of lining was light, due to long working hours(9.0h) and high intake rate, also leading to serious health risk (total DALY = 0.18a, total WTP = 14, 606) without isolation effect. This paper refined the health risk endpoint, improved the accuracy of assessment, and provided a reference for construction workers to strengthen dust prevention. Highlights: Tunnel construction adopting a roadheader will cause great dust for enclosed space. Quantitative health risk assessment is first applied to tunnel construction. The isolation of the dust mask significantly reduces the health risk caused by dust. 'Pneumoconiosis' and 'death' should be included in the health risks simultaneously.